2009
DOI: 10.1007/s10517-009-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell Therapy on Recovery of Cognitive Functions in Rats during the Delayed Period after Brain Injury

Abstract: We studied the effect of systemic transplantation of human stem cells from various tissues on cognitive functions of the brain in rats during the delayed period after experimental brain injury. Stem cells were shown to increase the efficacy of medical treatment with metabolic and symptomatic drugs for recovery of cognitive functions. They accelerated the formation of the conditioned defense response. Fetal neural stem cells had a stronger effect on some parameters of cognitive function 2 months after brain inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Previous studies revealed that MSC therapy may induce neurologic functional recovery in patients with TBI (27). The proliferotropic, angiogenic, neuroprotective, neutrophic, and regenerative effects of MSCs in rat trauma models were demonstrated in previous studies (16,33).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies revealed that MSC therapy may induce neurologic functional recovery in patients with TBI (27). The proliferotropic, angiogenic, neuroprotective, neutrophic, and regenerative effects of MSCs in rat trauma models were demonstrated in previous studies (16,33).…”
Section: Discussionmentioning
confidence: 93%
“…The “Beijing Declaration of IANR” (agreed upon at the IANR 2015 Conference in Tehran) declared as its fundamental tenet that “functional recovery is possible after central nervous system (CNS) injury and neurodegeneration” and noted that “cell therapies may become a key clinical therapeutic option for acute, subacute and/or chronic CNS diseases or damage” 5 . More than 30 types of cells have been identified through preclinical studies as having the capacity for neurorestoration 6 – 66 .…”
Section: Introductionmentioning
confidence: 99%
“…46 even without immunosuppression. Transient immunosuppression was shown to be sufficient to support engraftment and transplanted derived neurons were reportedly present 6 months post transplantation.…”
Section: Step 2 Immunosuppressionmentioning
confidence: 99%